STUDI KOMPARASI PEMIKIRAN ULAMA BADIUZZAMAN SAID NURSI DAN KITAB TA’LIM MUTA’ALIM TERHADAP PENDIDIKAN AKHLAK GENERASI MUDA - Maghfiroh, Naela (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This research is motivated by the impact of moral education of the younger generation which is starting to become the public spotlight due to abandoning moral values. So the writer is interested in studying the concept of moral education according to the cleric Badiuzzaman Said Nursi and the Book byTa'lim Muta'alim by the scholar Sheikh al-Zarnuzi. This study uses the type of literature study research. The approach used in this research is a historical approach. The method used to analyze the content is (content analysis). The purpose of this study is to find out how the concept of moral education according to the cleric Badiuzzaman Said Nursi and Kitab Ta'lim Muta'alim, and to find out the comparison of the concept of thought according to the cleric Badiuzzaman Said Nursi and the Kitab Ta'lim Muta'alim to the moral education of the younger generation.